2016
DOI: 10.14295/bds.2016.v19i2.1259
|View full text |Cite
|
Sign up to set email alerts
|

Microtensile bond strength of a universal adhesive to deep dentin

Abstract: <p><strong>Objective</strong>: This study evaluated the microtensile bond strength of a universal adhesive system applied to deep dentin under different bonding strategies. <strong>Material</strong> <strong>and Methods</strong>: Fifteen human third molars had the coronal portion removed exposing deep dentin and were assigned into 3 groups according to the adhesive system: G1(control): 2-steps totaletch (Adper Single Bond 2, 3M ESPE); G2: 1-step self-etch universal adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
1
8
1
Order By: Relevance
“…This chemical interaction between MDP and hydroxyapatite increase the mechanical strength of the adhesive interface in the self-etch strategy. (25) This agreement with Yoshida et al (26), Oznurhan et al in (16) whose found that with total-etch adhesive system the major elements that contribute to bond strength are intratubular resin-tag into demineralized intertubular dentine. This might be more difficult to happen in deep dentin because of the smaller amount of intertubular dentin to form the hybrid layer ,therefore deep dentin is more porous and retains more water within its enlarged tubule openings, which may avoid appropriate lateral bonding of the resin tags This disagreement with Ting et al (27) who reported that that the bond strength of one-step self-etch adhesive materials increased with increasing remaining dentin thickness (RDT), whereas that of two-step selfetch material was not affected by RDT.…”
Section: Effect Of Adhesive Systems and Dentin Level On Microtensile supporting
confidence: 75%
“…This chemical interaction between MDP and hydroxyapatite increase the mechanical strength of the adhesive interface in the self-etch strategy. (25) This agreement with Yoshida et al (26), Oznurhan et al in (16) whose found that with total-etch adhesive system the major elements that contribute to bond strength are intratubular resin-tag into demineralized intertubular dentine. This might be more difficult to happen in deep dentin because of the smaller amount of intertubular dentin to form the hybrid layer ,therefore deep dentin is more porous and retains more water within its enlarged tubule openings, which may avoid appropriate lateral bonding of the resin tags This disagreement with Ting et al (27) who reported that that the bond strength of one-step self-etch adhesive materials increased with increasing remaining dentin thickness (RDT), whereas that of two-step selfetch material was not affected by RDT.…”
Section: Effect Of Adhesive Systems and Dentin Level On Microtensile supporting
confidence: 75%
“…When a thin layer of adhesive is applied it inhibits the polymerisation due to decreased Oxygen content 48,49 . In contrast to it when the adhesive is applied in multiple layers it increases the bond strength and premature failures are also prevented 50 .…”
Section: Resultsmentioning
confidence: 99%
“…SEM images showed that the adhesive failure was dominant in both enamel and dentin groups and among all the tested adhesive systems. In the study by Gre et al, [ 37 ] the microtensile bond strength of a total-etch adhesive and universal adhesives was analyzed and it was indicated that most of the fracture modes were adhesive in all techniques . Further studies are recommended to assess the long-term durability of universal adhesive systems.…”
Section: Discussionmentioning
confidence: 99%